Spectral imaging for microbubble characterisation - Browning, R; Aron, M; Booth, A; Rademeyer, P; Wing, S; Brans, V; Shrivastava, S; Carugo, D; Stride, E (American Chemical Society, 2019)
Microbubbles stabilised by an outer lipid shell have been studied extensively for both diagnostic and therapeutic applications. The shell composition can significantly influence microbubble behaviour, but performing quantitative measurements of shell properties is challenging. The aim of this study was to investigate the use of spectral imaging to characterise the surface properties of a range of microbubble formulations representing both commercial and research agents. A lipophilic dye, C-Laurdan, whose fluorescence emission varies according to the properties of the local environment, was used to compare the degree and uniformity of lipid order in the microbubble shell and these measurements were compared with the acoustic response and stability of the different formulations. The method was found to be suitable for performing rapid and hence relatively high throughput measurements of microbubble surface properties. Interestingly, despite significant differences in lipid molecule size and charge, all of the different formulations exhibited highly ordered lipid shells. Measurements of liposomes with the same composition and the debris generated by destroying lipid microbubbles with ultrasound showed that these exhibited a lower and more varied lipid order than intact microbubbles. This suggests that the high lipid order of microbubbles is due primarily to compression of the shell as a result of surface tension and is only minimally affected by composition. This also explains the similarity in acoustic response between the formulations since microbubble dynamics are determined by the diameter and shell viscoelastic properties that are themselves a function of lipid order. Within each population, there was considerable variability in lipid order and response between individual microbubbles, suggesting the need for improved manufacturing techniques. In addition, the difference in lipid order between the shell and lipid debris may be important for therapeutic applications in which shedding of shell material is exploited e.g. for drug delivery.